Penyuluhan Tentang Pencegahan Praktik Prostitusi Online Di Madrasah Aliyah (MA) NU Tanjung Karang Kota Bandar Lampung - Choirul Salim; Aliyandi Aliyandi; Fitriyani Fitriyani; Umniyatus Selfiana (JPM: Jurnal Pengabdian Masyarakat, 2021)
ABSTRACT The problem of prostitution is nothing new in Indonesian society, currently online-based prostitution is increasingly rampant. Several incidents during the period of June 2014, recorded the number of cases of prostitution in Bandar Lampung, as many as 84 cases of which happened to children / adolescents. And in 2016 this increased to 156 cases. From the above problems, the authors conducted service in the form of counseling on the prevention of online prostitution practice at Madrasah Aliyah (MA) NU Tanjung Karang, this location was chosen because this educational institution is in the middle of the city of Bandar Lampung. The purpose of this service is to provide knowledge on the importance of preventing online prostitution among adolescents. From the results of the counseling activities carried out, MA NU Tanjung Karang students and students are increasingly aware of the problem of online prostitution that is rife in the city of Bandar Lampung, understand the importance of sex knowledge, the impact of online protection, ways of prevention and know the regulations related to online prostitution and extension participants become aware of the importance of always upholding religious teachings, moral values, customs and complying with applicable legal norms. Keywords: Counseling, Prevention, Online Prostitution